Combining qualitative methods in practice. Issue 4 (13th May 2014) - Simone Guercini, Professor; Carù, Antonella; Cova, Bernard; Pace, Stefano
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to discuss within a corporate context the advantages and limitations of combining different qualitative methods (namely consumers' introspection and observation) to grasp consumer experiences. Design/methodology/approach – The paper reflexively examines the evolution of a research process through which a team of researchers and a company tried to understand how the online consumer experience unfolds. The paper discusses the research process, the problems addressed and the way results were shared and acted upon within the company. Findings – The findings show how the search for and implementation of the combination of observation and introspection is rooted in the kinds of organizational change processes that allow companies to appropriate new methodological approaches and modify the conduct of their service innovation processes. Research limitations/implications – The paper is based on a single research project, analysed only retrospectively and reflexively. As to its implications, the proposed qualitative methods help mediate the collaborative interaction between researchers and the company during a research project. Practical implications – The research findings already have been appropriated and used by a multidisciplinary working group, operating within a corporate environment. Similarly, other companies can manage this type of research process following three major guidelines: prepare the cultural background, be iterative and maintain a conversation. Originality/value – The paper offers a unique account of the process of using combined qualitative methods within a company to understand consumer experiences.